MITIGATION OF NOISE POLLUTION IN URBAN AREAS BY STRATEGICALLY PLANTING TREES AND SHRUBS - Shahid Ali Khan; Kainat Fatima; Saddam Hussain; Muhammad Minhal Ali; Abdul Mannan; Nasim Iqbal Butt (Journal CleanWAS)
Noise is universally recognized as a significant source of environmental degradation in every culture. This paper provides an assessment of the literature on the detrimental impacts of noise pollution on the well-being of individuals. There is an introduction providing a broad definition of noise, followed by a discussion of the effect of noise pollution, the harmful consequences of noise on human health, and the techniques used to reduce noise pollution. In conclusion, this article reviews how this type of pollution can be mitigated and refers to vegetation’s aesthetic, ecological, and other benefits beyond its noise-blocking properties. The results of this research are significant on a personal and societal level in light of the detrimental impacts of noise pollution, and they may be helpful as a guide for planning in locations where such consequences are likely to materialize.